Comparative Study on Service Quality of Mobile Operators: An Approach of Multidimensional Profile Analysis - Panandikar, Sanjeev; Rajput, Rahul (Indian Journal of Marketing, 2005)
The telecom services have been recognized the world-over as an important tool for socio-economic development for a nation and hence telecom infrastructure is treated as a crucial factor to realize the socio-economic objectives in India. Accordingly, the Department of Telecom has been formulating developmental policies for the accelerated growth of the telecommunication services. The government of India recognizes that provision of world-class telecommunications infrastructure and information is the key to rapid economic and social development of the country. It is critical not only for the development of the Information Technology industry, but also has widespread ramifications on the entire economy of the country. The Indian Telecom sector is passing through a dynamic transitional phase, as it is clearly undergoing the operation of market forces of demand and supply. The sovereignty of consumers is quite evident through their revealed preference in favour of economically rational decisions.